Life Style As A Moderation Variable On The Influence Of Financial Literacy, And Self Control On Consumptive Behavior Perspective Of UNY Students - Ita Yuliana; Rosidah Rosidah (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This research aims to find out (1) the influence of life style in moderating financial literacy on students' consumptive behavior perspectives, and (2) the influence of life style on students' consumptive behavior perspectives with self-control. as moderator .This type of research is causal associative research using a quantitative approach. The population of this study was 1,100 students from the Class of 2021 UNY (FEB, FMIPA, and FISHIPOL). Sampling was based on the Taro Yamane formula of 294 students. Sampling uses techniques proportionate random sampling. The data collection method used is a questionnaire method which has been tested for validity and reliability with the help of SPSS Statistics 23 . The data analysis technique uses Moderated regression analysis Regression Analysisist (MRA).The research results prove that (1) life style weakens the influence of financial literacy on student consumptive behavior with a regression coefficient value of 0.023 and a sig value of 0.659 > 0.05. (2) life style weakens the influence of self-control on student consumptive behavior with a regression coefficient value of 0.008 and a sig value of 0.796 > 0.05. Keywords: Financial Literacy, Self Control, Consumptive Behavior, Life Style This research aims to find out (1) the influence of life style in moderating financial literacy on students' consumptive behavior perspectives, and (2) the influence of life style on students' consumptive behavior perspectives with self-control. as moderator .This type of research is causal associative research using a quantitative approach. The population of this study was 1,100 students from the Class of 2021 UNY (FEB, FMIPA, and FISHIPOL). Sampling was based on the Taro Yamane formula of 294 students. Sampling uses techniques proportionate random sampling. The data collection method used is a questionnaire method which has been tested for validity and reliability with the help of SPSS Statistics 23 . The data analysis technique uses Moderated regression analysis Regression Analysisist (MRA).The research results prove that (1) life style weakens the influence of financial literacy on student consumptive behavior with a regression coefficient value of 0.023 and a sig value of 0.659 > 0.05. (2) life style weakens the influence of self-control on student consumptive behavior with a regression coefficient value of 0.008 and a sig value of 0.796 > 0.05.